Pemberdayaan Masyarakat Sebagai Upaya Penanggulangan Permasalahan Kemiskinan - Rafa Fauziyah Rohyadi; Ati Kusumawati; Shahifa Kamila; Mohammad Raihan Pasya (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Poverty continues to be a relevant social issue in Indonesia, exacerbated by a multidimensional crisis. Handling poverty requires a holistic approach involving economic, social, cultural and political dimensions. Even though the government has launched prevention programs, poverty remains a problem that has not been fully resolved. Community empowerment is the key to overcoming poverty by providing resources and opportunities. Theoretical studies highlight the economic, social and cultural dimensions of poverty. Qualitative research methods with a phenomenological approach are used to understand the meaning and interpretation of the subjects involved. The research results show that community empowerment is needed to improve the quality of life and overcome poverty. Mitigation measures involve family protection, development of social security systems, and economic empowerment.